Development of Graded Vocabulary Parameters for Chinese BIPA based on Frequency - Lu, Yingxuan; Damayanti, Vismaia Sabariah; Sastromiharjo, Andoyo; Mulyati, Yeti (ppjbsip, 2023)
This study addresses three main inquiries: 1) How to effectively classify Indonesian words based on frequency? 2) What are the distinctive characteristics of words across various proficiency levels? 3) How is vocabulary utilized in BIPA teaching materials? The article aims to create a graded vocabulary list to assess lexical complexity by examining word distribution in texts. Using a quantitative descriptive method, high-frequency words are chosen from eight widely-used Chinese BIPA language sources and categorized into frequency tiers using the %WF>=P method. The graded word list is then applied to BIPA textbooks to assess discourse difficulty. A total of 5,700 word families are organized into five proficiency grades based on cumulative frequencies. Analysis reveals that high-frequency words show a balanced distribution across materials, with a prevalence of polysemous words and concentrated word lengths. Low-frequency words are more domain-specific, emphasizing specific meanings and displaying a broader range of lengths. Examining word usage in different texts indicates alignment between Indonesian teaching materials, academic journals, newspapers, and audio-visual materials with BIPA textbooks. Speech scripts and public documents are more suitable for advanced teaching, while social media language differs notably from BIPA textbooks.